Methodological proposal for Dramatisation class in the primary teaching curriculum, Early Years Education - Ruiz de Velasco Gálvez, Ángeles; Abad Molina, Javier (Pulso. Revista de educación, 2007)
This paper develops an experience carried out during this course year, 2006/07, within the subject Dramatisation. This subject belongs to the Infant Education syllabus, at Centro Superior de Estudios Universitarios La Salle, Universidad Autónoma Madrid. The proposal offers a methodological approach which diversifi es the offer of theoretical and practical assignments that students have to do throughout the subject both in its contents and in the way to develop them. With this format, we intend to encourage the students interest and curiosity regarding their own work and that of their classmates.
Keywords: Infant Education; Teacher Training Studies; Dramatization; Symbolic Play